Employees’ Perceptions of Internal CSR and External CSR towards Organizational Citizenship Behaviour - Bista, Sita (Nepal Journal of Multidisciplinary Research, 2022)
When employees "go above and beyond" or "give their all" at work, they see their jobs as more than just a salary, and they are willing to do anything they can to make their workplace more productive, even if such efforts are not part of their job descriptions. Such behaviors can be attributed to an individual's disposition, but companies can also encourage them by fostering a serene environment. As a result, the purpose of this study is to look into the impact of employees' perceptions of corporate social responsibility on their affective commitment, job satisfaction, and organizational citizenship activity. From six different banks, 260 employees filled up data. The finding shows that Internal CSR is weaker than External CSR in those companies.